Co-planting Brassica napus and Salix nigra as a phytomanagement alternative for copper contaminated soil. (September 2021) - Massenet, Aleena; Bonet, Amandine; Laur, Joan; Labrecque, Michel
Abstract: Phytoremediation of copper contaminated soil poses particular difficulties because of the low Cu mobility in the soil. Although several plant species, such as willows or Brassicaceae, have been used in the phytomanagement of abandoned brownfields, certain trace elements, such as copper often remain difficult to treat or remove from contaminated soils. An experiment was conducted under semi-controlled conditions to test the phytoremediation potential of co-planting two crop species, Brassica napus L. and Salix nigra 'S05', in soil spiked with two concentrations of Cu (500 mg kg −1 and 800 mg kg −1 ). Particular attention was given to the potential of 1) the co-plantation design and 2) uprooting, to efficiently mimic the remediation of a Cu-contaminated soil. Results showed that most Cu was found in plant roots and that the polyculture treatment produced the most overall biomass and maximum stabilization and extraction of Cu of the three treatments tested, regardless of contamination level. Highlights: Brassica napus and  Salix nigra 'S05' were grown together or separately to compare their Cu phytoremediation potential. Polyculture treatment maximizes both Cu stabilization and extraction. Collecting uprooted plants would remove the most copper from the soil. Willows were more affected by copper soil concentration.